2018
DOI: 10.3989/aespa.1993.v66.474
|View full text |Cite
|
Sign up to set email alerts
|

Tipos cerámicos y Geoquímica: el Castrelín de San Juan de Paluezas (León)

Abstract: Se discuten algunos métodos de caracterización mineralógica de cerámicas, buscando el establecimiento de tipos que permitan combinar los datos morfométricos y la funcionalidad de las vasijas con su estructura físico-química. Para ello se utilizan varias categorías cerámicas, análisis de fluorescencia de rayos X y un tratamiento de los datos con análisis multivariante de los óxidos mayoritarios y minoritarios en la composición de la cerámica. Los materiales analizados proceden de castros prerromanos de la Zona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Therefore, it seems logical to point to a local origin of the raw materials used for the kiln manufacture that had been suggested for the vessels. Studies of the provenance indicate that the majority of ceramic-made objects were made from local clays (Galván Martínez et al 1993;Little 1990), although settlements have also been found that acquire most of their vessels (de Groot and González-Álvarez 2021). This could be understood as typical of Iron Age pottery production, which would have been largely made in domestic contexts, of a family or artisanal nature, and with a largely regional or local distribution (Rey Castiñeira et al in press).…”
Section: Raw Materials Procurementmentioning
confidence: 99%
“…Therefore, it seems logical to point to a local origin of the raw materials used for the kiln manufacture that had been suggested for the vessels. Studies of the provenance indicate that the majority of ceramic-made objects were made from local clays (Galván Martínez et al 1993;Little 1990), although settlements have also been found that acquire most of their vessels (de Groot and González-Álvarez 2021). This could be understood as typical of Iron Age pottery production, which would have been largely made in domestic contexts, of a family or artisanal nature, and with a largely regional or local distribution (Rey Castiñeira et al in press).…”
Section: Raw Materials Procurementmentioning
confidence: 99%